The RNA‐binding protein MEX3A is a prognostic factor and regulator of resistance to gemcitabine in pancreatic ductal adenocarcinoma. Issue 2 (24th November 2020) - Panzeri, Valentina; Manni, Isabella; Capone, Alessia; Naro, Chiara; Sacconi, Andrea; Di Agostino, Silvia; de Latouliere, Luisa; Montori, Andrea; Pilozzi, Emanuela; Piaggio, Giulia; Capurso, Gabriele; Sette, Claudio
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive cancer. Most patients present with advanced disease at diagnosis, which only permits palliative chemotherapeutic treatments. RNA dysregulation is a hallmark of most human cancers, including PDAC. To test the impact of RNA processing dysregulation on PDAC pathology, we performed a bioinformatics analysis to identify RNA‐binding proteins (RBPs) associated with prognosis. Among the 12 RBPs associated with progression‐free survival, we focused on MEX3A because it was recently shown to mark an intestinal stem cell population that is refractory to chemotherapeutic treatments, a typical feature of PDAC. Increased expression of MEX3A was correlated with higher disease stage in PDAC patients and with tumor development in a mouse model of PDAC. Depletion of MEX3A in PDAC cells enhanced sensitivity to chemotherapeutic treatment with gemcitabine, whereas its expression was increased in PDAC cells selected upon chronic exposure to the drug. RNA‐sequencing analyses highlighted hundreds of genes whose expression is sensitive to MEX3A expression, with significant enrichment in cell cycle genes. MEX3A binds to its target mRNAs, like cyclin‐dependent kinase 6 (CDK6), and promotes their stability. Accordingly, knockdown of MEX3A caused a significant reduction in PDAC cell proliferation and in progression to the S phase of the cell cycle. These findings uncover a novel role for MEX3A in the acquisition and maintenance of chemoresistance by PDAC cells, suggesting that it may represent a novel therapeutic target for PDAC. Abstract : RNA dysregulation is a hallmark of most human cancers, including PDAC. We identify the RNA‐binding protein MEX3A as prognostic factor in PDAC. MEX3A regulates stability of transcripts for cell cycle proteins, such as CDK6, and promotes cell cycle progression and resistance to chemotherapeutic treatments.